(untitled) (Journal of the College of Basic Education, 2022)
Actually sensation seeking is considered to be an important factor in developing and achieving of self consistency. In case of enhancing for the individual mind to be effected by rich sensitive environment which in turn take part in allowing the human abilities and powers to be discovered , this means that a strong relationship between sensation seeking and self consistency pushes the individuals to participate actively in achieving and right decision making towards a daily life –faced situations . This research aims to the following 1- Setting up the tools for measuring the sensation seeking of secondary school students. 3- Signify the conditions of the self consistency according to two variables of type (males –females) and specialization (scientific – literary) . 4- Setting up a tool for measuring the self consistency of secondary schools students. 6- Notify the circumstances of self consistency according to two variables:-type ( males –females ) and specialization (scientific –literary) 7- Finding a relationship between the self consistency and sensation seeking for the secondary school students. on the samples of 300 secondary school students that hve been selected randomly at the province of Diayala . After analyzing and processing the date statistically by using T tests on one sample and T tests on two independent samples , in addition to test of difference analysis .All those tests concluded the research with the following results :- 1-The secondary school students are featured with sensation seeking . 2-There is no semantic statistic meaningful difference in the sensation seeking on the basis of the type variable. 3- There is no semantic statistic meaningful difference in the sensation seeking on the basis of the specialization variable. 4 – The secondary school students are featured with self consistency. 5- The females are more self consistent than the males. 6-There is a semantic statistic meaningful difference in the self consistency on the side of the scientific specialization. 7 –There is a positive associated relationship between the self consistency and sensation seeking of the secondary school students. In the light of those results , the researcher has some recommendations such as the following :- Presenting a great efforts to include the items and means of sensation seeking inside the curriculum setting to attract the students attention and increasing their concentration on the information inside the classroom . Doing the best and considerable steps to develop the self consistency by acknowledging the teachers , fosters , fathers of students with the effective factors in process of establishing an unified consistent system for the pupils from the early stage of their childhood. Here the researcher has some suggestions relevant to the essentials of the subject matter. It is important to get study about the sensation seeking and its relationship with other variables such as the self evaluation, the mood , emotionlessness ,the activity and the effectiveness . Make a study about the self consistency and its relationships with self –trust , hope, and the criteria of dealing with parenting